2019
DOI: 10.1159/000495688
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Education on Hypothermia Delivery during Neonatal Transport

Abstract: Background: Moderate therapeutic hypothermia (TH) initiated within 6 h of life reduces adverse neurodevelopmental outcomes in infants after perinatal hypoxic ischaemic insult. For infants born in non-tertiary centres, TH may be initiated manually en route to a neonatal intensive care unit (NICU). However, both over- and undercooling is reported with this strategy, precluding some infants from the benefits of TH. Objectives: To evaluate the impact of a region-wide educational programme on the safety and efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Outborn infants frequently do not have access to cooling within the cri cal me window and are either not offered TH or reach the target temperature later [11,24,25]. Strategies to overcome the delayed TH onset by ac ve or passive cooling prior to arrival at the cooling center require training and bring along reduced efficiency and risk of overcooling [26]. To further inves gate the most severely affected infants -the subgroup receiving TH -we conducted a sensi vity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Outborn infants frequently do not have access to cooling within the cri cal me window and are either not offered TH or reach the target temperature later [11,24,25]. Strategies to overcome the delayed TH onset by ac ve or passive cooling prior to arrival at the cooling center require training and bring along reduced efficiency and risk of overcooling [26]. To further inves gate the most severely affected infants -the subgroup receiving TH -we conducted a sensi vity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Many attempts have been made to apply a standardised protocol in the treatment of outborns eligible for therapeutic hypothermia. While outcomes may be influenced by local neonatal transport resources, several studies demonstrated that education and training can improve neonatal outcomes 49,50 . Bellini et al 51 suggested that an experienced transport team can successfully start passive cooling before admission to a referral centre.…”
Section: Discussionmentioning
confidence: 99%
“…While outcomes may be influenced by local neonatal transport resources, several studies demonstrated that education and training can improve neonatal outcomes. 49,50 Bellini et al 51 suggested that an experienced transport team can successfully start passive cooling before admission to a referral centre. In contrast, Reaney et al 52 stated that passive cooling does not consistently achieve adequate control of body temperature for outborn infants.…”
Section: Ta B L E 6 Summary Ofmentioning
confidence: 99%